2012 IEEE 31st Symposium on Reliable Distributed Systems 2012
DOI: 10.1109/srds.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

Model-Driven Comparison of State-Machine-Based and Deferred-Update Replication Schemes

Abstract: Abstract-In this paper, we analyze and experimentally compare state-machine-based and deferred-update (or transactional) replication, both relying on atomic broadcast. We define a model that describes the upper and lower bounds on the execution of concurrent requests by a service replicated using either scheme. The model is parametrized by the degree of parallelism in either scheme, the number of processor cores, and the type of requests. We analytically compared both schemes and a nonreplicated service, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Firstly, as our previous work [9] showed that neither the state-machine-based nor deferred-update replication scheme was superior, we were eager to combine these two into a single algorithm to bring together the best of both worlds. Secondly, we are not aware of any prior research on applying transactional semantics to state machine replication for increased expressiveness.…”
Section: A Motivations and Contributionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly, as our previous work [9] showed that neither the state-machine-based nor deferred-update replication scheme was superior, we were eager to combine these two into a single algorithm to bring together the best of both worlds. Secondly, we are not aware of any prior research on applying transactional semantics to state machine replication for increased expressiveness.…”
Section: A Motivations and Contributionsmentioning
confidence: 99%
“…We added the HTR functionality to Paxos STM [9] which is an object-based DTM system that we developed to compare the SM and TR replication schemes. It builds on JPaxos [24]a highly optimized implementation of the Paxos algorithm [25].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations